Genome-wide identification of the COBRA-like gene family and expression pattern analysis under abiotic stresses of Sorghum bicolor (L.) - Liu, Shipeng; Liang, Shuang; Jing, Tingrui; Guo, Xinyi; Wang, Hairuo; Ma, Quan; Wang, Junshen; Wang, Kai; He, Xiaolong; Zhao, Haibing; Jiang, Wenting; Zhang, Xiangqian (Frontiers in Plant Science, 2025)
IntroductionCOBRA-Like (CBL) genes encode glycosylphosphatidylinositol (GPI) -anchored proteins specific to plants that play important roles in cellulose biosynthesis in primary and secondary cell walls.MethodsThis study used a bioinformatics approach to characterize the CBL family genes in Sorghum bicolor (S. bicolor) at the genome-wide level to investigate their potential functions in S. bicolor development.ResultsThe results revealed the identification of 10 CBL genes in the BTx623 and E048 S. bicolor genomes, respectively. A comparative analysis of conserved Motifs revealed that all CBL family genes in S. bicolor possess CCVS conserved structural domains. Phylogenetic analysis revealed that the family can be divided into two subfamilies, with genes within each subfamily exhibiting similar gene structures and physicochemical properties. Whole Genome Duplication (WGD) played an important role in the expansion of SbCBL gene family. The tissue-specific expression patterns of SbCBL genes suggest varying expression levels across different organs and tissues in S. bicolor, with SbCBL1, SbCBL5, and SbCBL9 showing significantly higher expression levels in roots. PEG and NaCl treatments significantly affected SbCBL expression levels. SbCBL4 expression increased after PEG treatment, while SbCBL9 expression decreased after NaCl treatment.ConclusionsOverall, this study provides new insights into the role of the CBL gene family in S. bicolor.